PENGAKUAN PENGUASAAN DAN PENDUDUKAN TANAH TANPA ALAS HAK KEPEMILIKAN YANG BERAKIBAT SENGKETA: STUDI KASUS PUTUSAN MA NO. 2511K/PDT/1995 TANGGAL 09 SEPTEMBER 1997 - MARIA FARIDA NAIBAHO (PREMISE LAW JURNAL, 2015)
Ownershipofhouse or land tenure by an individual or a community must be based on the strong and valid proof of ownership and one of which is the right to land and house. Shouldsomeone have right to land, it must be supported by evidence, can be either a certificate, a non-certificate written evidence of the right, and/or a recognition/description of reliable truth. The conclusion drawn from the decision of court was clear that the owner who has the right, in this dispute, to the land is Haji Basyarudin, this decision is also reinforced by the result of deliberation in the form of Letter of Certification/Peace, and up to the decision of State Court Level I and is reinforced againby the Decisionof the Supreme CourtNo.2511K / PDT / 1995 dated 09 September 1997. The in kracht van gewijsde (legally enforceable) decision can proceed to the stage of execution. Keywords: Land Tenure, Land Registration